RAT REPELLENT IN RICE FIELDS USING SOUND SENSORS AND SOLAR-POWERED BEN 5M-MFR AUTONIC SENSORS - Alfad, Mochamad Alfin Bachtiar; Sulistiyowati, Indah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Rice is a staple food in Indonesia, but pests such as rats and birds often cause significant crop failures. This research developed a technological solution using solar power to deter these pests and optimize yields. Method: The study utilized a research and development approach, testing components such as solar panels, a timer, an FC-04 sound sensor, and an autonic BEN5M-MFR sensor. Results: The results indicate that the sensor can detect pests within a 7m range, triggering ultrasonic waves regulated by the timer to effectively repel rats and birds. The solar panel maintained a consistent 13V throughout the day, and the battery powered the system for 7 hours, demonstrating the viability of the solar-powered design to meet operational requirements. Novelty: This innovation contributes to enhancing food security by mitigating the impact of pests on rice cultivation through the integration of renewable energy technology.